Neurological Complications of Primary Varicella Zoster Virus Infection in Children- Case Reports - Mihai, Raluca; Mavrodin, Mihaela; Fabrian, Mihalcea; Dumitrescu, Anca; Cambrea, Simona Claudia (International Journal of Pediatrics and Child Health, 2023)
Introduction: VZV is a human neurotropic alpha herpes virus, and humans are the only reservoir. Infection can involve any part of the nervous system. The incidence of neurological manifestations associated with VZV is 1-3 per 10,000 cases. The clinical manifestations of varicella-zoster virus (VZV) infections of the central nervous system (CNS) include aseptic meningitis, encephalitis, cerebral infarction associated with granulomatous vasculitis, myelitis, and multiple cranial neuropathies. The aim of this study, by reporting a series of 5 cases of chickenpox hospitalized in the Clinical Infectious Diseases Hospital from Constanta, is to demonstrate some of the neurological complications of varicella zoster virus infection in children, highlighting the importance in early recognition and prompt initiation of specific treatment. Case reports: Two cases of acute post-infectious cerebellitis in children aged 7 and 9 years were hospitalized in our clinic. The clinical picture presented by the 2 patients consisted of fever, headache, altered consciousness with coordination and gait disorders. Other two cases of acute transverse myelitis, a 12-year-old boy, with onset in a febrile state at 9 days post varicella, initially with left knee pain associated with hypo-hyperaesthesia-like tenderness disorders, subsequently decreased lower limb muscle strength and bladder sphincter disorders. In the case of the second patient, the onset was on day 12 of evolution, with gait and balance disorders, with acute urine retention. A fifth case, a 2-year-old child, hospitalized for altered consciousness with drowsiness, listlessness, photophobia and fever with suspicion of encephalitis. Neither of the children didn’t reciveoral acyclovir from de onset of the rash. Conclusion; Clinicians should be aware of the neurologic complications of VZV infection, because early recognition and initiation of acyclovir therapy is necessary for these disorders.